KONSEP PENDIDIKAN ISLAM DAN FUNGSI SERTA PERANAN PTAI - Azhar, Sophia (Inspiratif Pendidikan, 2017)
This paper describes the initial view of the concept of Islamic education and the role of Islamic Higher Education on Human Resources. Further mentioned also what has been expressed by Prof. Quraish Shihab at al-Markaz al-Islamiy, Makassar in the 1900s on our concept and understanding of human resources. With this understanding is expected to facilitate the retrieval of a conclusion of what are the main ideas that must exist in a concept of education ideally. Furthermore, the search for the ideal concept of ideal Islamic education preceded by the exposure of the widely disseminated Islamization of knowledge throughout the world-though it does not escape the pros and cons. With this discussion concluded there will be hope for Islamic religious college to reveal its function and role.